2006
DOI: 10.1029/2006gl026106
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave anisotropy of the northeast Indian lithosphere

Abstract: Analysis of SKS/SKKS phases in the northeast India region provides the first results using digital data, from the southern side of the India‐Asia collision zone. Our analysis reveals detectable anisotropy in the study region, contrary to negligible anisotropy reported in southern Tibet. The direction of anisotropy is E‐W within the Himalaya and its foredeep, N‐S in the Indo‐Burma convergence zone and NE‐SW close to the Shillong plateau. While lithospheric deformation due to finite strain induced by collision s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 17 publications
6
46
0
Order By: Relevance
“…It is also consistent with a recent GPS study that implies a slip rate of ~5 mm/yr across the Badapani-Tyrsad shear zone (Jade et al, 2007). The northeast-striking left-slip faults may root all the way into the mantle, as suggested by the northeast-trending fastest direction of shear-wave polarization below the Shillong Plateau (Singh et al, 2006) and seismicity within the whole crust and upper mantle (Mitra et al, 2005).…”
Section: Cenozoic Deformationsupporting
confidence: 91%
See 1 more Smart Citation
“…It is also consistent with a recent GPS study that implies a slip rate of ~5 mm/yr across the Badapani-Tyrsad shear zone (Jade et al, 2007). The northeast-striking left-slip faults may root all the way into the mantle, as suggested by the northeast-trending fastest direction of shear-wave polarization below the Shillong Plateau (Singh et al, 2006) and seismicity within the whole crust and upper mantle (Mitra et al, 2005).…”
Section: Cenozoic Deformationsupporting
confidence: 91%
“…Strikeslip focal mechanisms dominate the Shillong Plateau; the seismicity occurs across all depths of the crust and may even be in the uppermost mantle (Kayal and De, 1991;Mitra et al, 2005;Drukpa et al, 2006). Shear wave anisotropy in northeastern India exhibits an east-west fastest direction below the Himalaya, a north-south fastest direction across the Indian-Burma Range, and a northeast-southwest fastest direction across the Shillong Plateau (Singh et al, 2006), all of which correlate well with surface traces of Cenozoic faults (also see Kumar et al, 1996).…”
Section: Regional Geologymentioning
confidence: 99%
“…The form of upper-mantle deformation at depths down to the top of the transition zone (410 km) can be discerned from seismic anisotropy detailed using shear-wave splitting analyses (e.g., Silver, 1996;Savage, 1999 (Lev et al, 2006;Sol et al, 2007;Wang et al, 2008). Shear-wave splitting analyses from northeastern India are consistent with generally E-W upper-mantle fabrics south of Tibet and west of the syntaxis (Singh et al, 2006(Singh et al, , 2007. These results were derived from data collected at temporary seismic deployments in China and India, and such deployments are not currently possible in Myanmar.…”
Section: Arakan Slab Segmentationmentioning
confidence: 96%
“…The lack of anisotropy beneath southern Tibet was mainly explained by an isotropic nature of the Indian tectonic plate or a lack in the ability of SKS phases to sample the anisotropy due to a sub-vertical mantle shear strain field created by downwelling Indian lithosphere Sandvol et al, 1997). However, the hypothesis of an isotropic nature of the Indian lithosphere was contradicted in various studies (Singh et al, 2006Kumar and Singh, 2008), and significant anisotropy is reported beneath Tibet in the region of null measurement (Gao and Liu, 2009;Singh et al, 2016).…”
Section: Origin Of Anisotropy In the Southeastern Tibetan Regionmentioning
confidence: 99%